2009
DOI: 10.1002/art.24360
|View full text |Cite
|
Sign up to set email alerts
|

Variants within MECP2, a key transcription regulator, are associated with increased susceptibility to lupus and differential gene expression in patients with systemic lupus erythematosus

Abstract: Objective. Both genetic and epigenetic factors play an important role in the pathogenesis of lupus. The aim of this study was to examine methyl-CpG-binding protein 2 gene (MECP2) polymorphisms in a large cohort of patients with lupus and control subjects, and to determine the functional consequences of the lupusassociated MECP2 haplotype.Methods. We genotyped 18 single-nucleotide polymorphisms within MECP2, located on chromosome Xq28, in a large cohort of patients with lupus and control subjects of European de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 42 publications
5
81
0
1
Order By: Relevance
“…Multiple studies point to an X-chromosomal role in lupus (e.g. [119]). Using the fourcore genotypes with transgenic mice predisposed to lupus reveals accelerated lupus in mice with two X chromosomes relative to females with only a single X chromosome [120].…”
Section: (A) Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Multiple studies point to an X-chromosomal role in lupus (e.g. [119]). Using the fourcore genotypes with transgenic mice predisposed to lupus reveals accelerated lupus in mice with two X chromosomes relative to females with only a single X chromosome [120].…”
Section: (A) Systemic Lupus Erythematosusmentioning
confidence: 99%
“…RTT is a devastating disorder that afflicts 1 in 10,000 females and whose symptoms are largely neurodevelopmental (11). Based on the limited immunological studies on RTT patients, however, hints of immunological abnormalities have gradually emerged: Polymorphisms within the human mecp2 locus have recently been associated with an increased susceptibility to systemic lupus erythematosus (12,13) and primary Sjögren's syndrome (14), suggesting that mecp2 gene mutations may also contribute to the pathogenesis of inflammatory diseases, and a cohort study also demonstrated significantly elevated levels of IgG against food proteins in the sera of RTT patients (15), which may reflect the possibility of gut inflammation or breakdown of the intestinal barrier; most intriguingly, the transplantation of wild-type (WT) bone marrow successfully arrested RTT disease in MeCP2-null mice (16). Nevertheless, apart from these correlative studies, MeCP2's causative role in immune regulation remains largely unexplored.…”
mentioning
confidence: 99%
“…Polymorphisms in MECP2 may have relevance to the epigenetic DNA methylation changes found in lupus and discussed below. There is evidence for altered methylation in SLE, (Webb, 2009) as well as differential expression of potentially methylated genes, although, as with IRAK1, a contributing causative SNP is not immediately obvious. Indeed, it is possible that both of these strong candidates contribute to the effect.…”
Section: Chromosome 19mentioning
confidence: 99%